Obesity and Operative Time in Primary Total Joint Arthroplasty - Raphael, Ibrahim J.; Parmar, Mayank; Mehrganpour, Neema; Sharkey, Peter F.; Parvizi, Javad (The Journal of Knee Surgery, 2013)
Obesity has been associated with osteoarthritis and increased morbidity and mortality. Most joint arthroplasty patients have a high body mass index (BMI). Some surgeons are reluctant to operate on obese patients due to technical difficulties and the anticipated higher complication rate. The purpose of this prospective study was to determine whether obesity is associated with longer operative times. We attended 100 consecutive primary total joint arthroplasties. Patients were divided into four groups depending on their BMI: the normal group (BMI: 18 to 24.9 kg/m2), the overweight group (BMI: 25 to 29.9 kg/m2), the obese group (BMI: 30 to 39.9 kg/m2), and the morbidly obese group (BMI ≥ 40 kg/m2). Anesthesia type and time, duration of surgery, time needed for scrubbing, draping, and transferring the patient to the operating table were all documented. The mean operative time for total hip arthroplasty (THA) was significantly increased in morbidly obese patients (R2 = 0.197, p = 0.003). The mean scrubbing time for total knee arthroplasty varied with BMI (p = 0.028). Time to administer spinal anesthesia was significantly increased in morbidly obese patients (R2 = 0.1466, p = 0.018). Morbid obesity is associated with a significant increase in the time needed to administer spinal anesthesia and the overall time needed to perform a THA.
Keywords: obesity; operative time; arthroplasty; complications; orthopedic